Taraxasterol protects hippocampal neurons from oxygen-glucose deprivation-induced injury through activation of Nrf2 signalling pathway - Yun He; Kaifu Jiang; Xue Zhao (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Cerebral ischemia/reperfusion (I/R) injury is a brain injury following ischaemic stroke that is associated with oxidative stress. Taraxasterol, a natural product, has been shown to have anti-oxidative and neuro-protective effects. However, the role of taraxasterol in cerebral I/R injury remains unknown. Primary hippocampal neurons were subjected to oxygen-glucose deprivation/reperfusion (OGD/R) to induce cerebral I/R injury in vitro. Cell viability of hippocampal neurons was measured CCK-8 assay. Reactive oxygen species (ROS) production and MDA generation were measured to reflect oxidative stress. Western blotting was performed to evaluate the expressions of bax, bcl-2, NF-E2-related factor 2 (Nrf2), haem oxygenase (HO-1), NAD(P)H:quinone oxidoreductase 1 (NQO-1) and GPx-3. Caspase-3 activity was measured to assess cell apoptosis. Hippocampal neurons were treated with ML385 to inhibit Nrf2 signalling pathway. Our results showed that taraxasterol improved OGD/R-caused decrease in cell viability of hippocampal neurons. In addition, taraxasterol significantly suppressed ROS production and MDA generation in OGD/R-induced hippocampal neurons. Taraxasterol resulted in a significant decrease in caspase-3 activity and bcl-2 expression, as well as increase in bax expression. Furthermore, taraxasterol induced the Nrf2 nuclear accumulation and expressions of HO-1, NQO-1 and GPx-3 in OGD/R-induced hippocampal neurons. Notably, inhibition of Nrf2 signalling reversed the protective effects of taraxasterol on OGD/R-induced hippocampal neurons injury. In conclusion, these findings indicated that taraxasterol protected hippocampal neurons from OGD/R-induced oxidative stress and cell apoptosis via regulating the Nrf2 signalling pathway.